Estimation of Nitrogen (N) Storage in Seagrass in The East and North Coastal Waters of Bintan Island - Ismi Dwi Yulianti; Andi Zulfikar; Winny Retna Melani (Journal of Marine and Coastal Science, 2026)
Seagrass has high primary productivity and is highly dependent on the availability of nitrogen as the main nutrient that supports growth, photosynthesis, and biomass, including in the waters of Bintan, Indonesia. This research was conducted to determine the density, biomass, and nitrogen content of seagrass, as well as the influence of density and biomass on nitrogen storage to support sustainable conservation management in the Eastern and Northern regions of Bintan Island. The research was conducted from August 2024 to May 2025 by taking seagrass samples using the nested hierarchical design method based on systematic random sampling. Nitrogen measurements are carried out using the Kjeldahl method which converts organic nitrogen into ammonium sulfate. Based on this research, the highest density (816.1 stands/m2) and biomass (138.56 g/m2) of seagrass were in Pengudang. The lowest density and biomass were in Berakit_2 with values of 106.8 stands/m2 and 19.03 g/m2, respectively. The highest nitrogen (0.758%) was found in 2 locations, namely Pengudang and Teluk Bakau_2, while the lowest nitrogen (0.359%) was in Berakit_1. Based on regression analysis, the density and biomass of seagrass had a significant effect on nitrogen storage with a regression value of 0.642.